Instructional Supervision as Dialogue: Utilizing the Conversation of Art to Promote the Art of Conversation - Zach Kelehear (Arizona State University, 2010)
The degree to which instructional supervisors encourage reflection by teachers is in large part a function of both the supervisorâs and teacherâs use of the art of conversation. The author juxtaposes the Concern Based Adoption Model theory for innovation with the Feldman Method for art criticism to support reflection as aesthetic. Reflection that is grounded in an arts-based methodology may embrace both the technical and aesthetic dimensions of teaching and supervision. The author concludes that utilizing the language of art may support reflection that attends to the needs of the teacher and the needs of the students.